1925 Ind. Acts 497, § 8 - (:unkn) unknown (My University, 1925)
Prohibited the sale, barter, hire, lend, or giving of pistols or revolvers to minors under the age of twenty-one. Violators guilty of a misdemeanor, fined not more than one hundred dollars, or imprisoned not more than three months, or both fine and imprisonment.
Keywords: CARRY - CONCEALED; TRANSFER - MINORS